Synthesis of quinoline derivatives as diabetic II inhibitors and molecular docking studies. Issue 18 (15th September 2019) - Taha, Muhammad; Sultan, Sadia; Imran, Syahrul; Rahim, Fazal; Zaman, Khalid; Wadood, Abdul; Ur Rehman, Ashfaq; Uddin, Nizam; Mohammed Khan, Khalid
Graphical abstract: Abstract: In searchof the potenttherapeutic agent as an α -glucosidase inhibitor, we have synthesized twenty-five analogs (1 –25) of quinoline-based Schiff bases as an inhibitoragainst α-glucosidase enzyme under positive control acarbose (IC50  = 38.45 ± 0.80 µM). From the activity profile it was foundthat analogs 1, 2, 3, 4, 11, 12 and 20 with IC50 values 12.40 ± 0.40, 9.40 ± 0.30, 14.10 ± 0.40, 6.20 ± 0.30, 14.40 ± 0.40, 7.40 ± 0.20 and 13.20 ± 0.40 µMrespectively showed most potent inhibition among the series even than standard drug acarbose (IC50  = 38.45 ± 0.80 µM). Here in the present study analog 4 (IC50  = 6.20 ± 0.30 µM) was found with many folds better α-glucosidase inhibitory activity than the reference drug. Eight analogs like 5, 7, 8, 16, 17, 22, 24 and 25 among the whole series displayed less than 50% inhibition. The substituents effects on phenyl ring thereby superficially established through SAR study. Binding interactions of analogs and the active site of ligands proteins were confirmed through molecular docking study. Spectroscopic techniques like 1 H NMR, 13 C NMR and ESIMS were used for characterization.